(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
It provides information about psychological and pedagogical methods of studying children with hearing impairment. Sign pedagogy uses various research methods to develop and study the process of education for children with hearing impairment.